2015
DOI: 10.1179/1074935714z.0000000001
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to community ambulation in patients with chronic stroke

Abstract: The focus of gait rehabilitation for walking in real-life settings should vary according to different aspects of gait performance. Investigation of factors related to impairments specific to community ambulation or activity participation may be helpful in determining and targeting appropriate treatment for gait rehabilitation. Objective To investigate the relationship between community ambulation and factors determining gait ability. Methods Forty-six outpatients with a previous stroke participated in a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
2
34
0
2
Order By: Relevance
“…Although BBS scores were associated with WSR values among those who used an assistive device and those who did not, the association appears stronger for those who used a device (Spearman’s r =0.39 for no assistive device and 0.65 for assistive device, p < 0.001). Lee et al [14] previously reported an association between balance impairments and the ability to increase WS in individuals with chronic stroke who did not require an assistive device. Our findings expand on that work by demonstrating that this relationship exists, and may actually be stronger, in those who require an assistive device for ambulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although BBS scores were associated with WSR values among those who used an assistive device and those who did not, the association appears stronger for those who used a device (Spearman’s r =0.39 for no assistive device and 0.65 for assistive device, p < 0.001). Lee et al [14] previously reported an association between balance impairments and the ability to increase WS in individuals with chronic stroke who did not require an assistive device. Our findings expand on that work by demonstrating that this relationship exists, and may actually be stronger, in those who require an assistive device for ambulation.…”
Section: Discussionmentioning
confidence: 99%
“…[14] However, slower walkers are less able to increase their speed on demand [6] and also demonstrate reduced balance compared to faster walkers. [1] This suggests that individuals post-stroke may be unable to access their “reserve” due to diminished balance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the majority of stroke survivors gain "independent walking" [3], up to 50% of chronic stroke survivors regularly request a companion when walking outdoors [4]. Mobility issues such as reduced balance [5], walking speed and endurance [6,7], and falls [8] have been demonstrated in people several years after stroke. The effect on individuals, health care systems, and society suggest a greater need to focus attention on the long-term consequences, management, and rehabilitation of people with stroke to reduce the global stroke burden is thus needed [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the clinicians should identify relevant variables and assessment tools to predict independence of ambulation. Community gait ability is related to several factors such as perception, balance, and muscle strength [22]. The TUG test consists of consecutive tasks as standing up from a chair, walking forward, turning, coming back, and sitting down on the chair.…”
Section: Discussionmentioning
confidence: 99%